EKSPLORASI ALAT MUSIK GARANTUNG PADA PEMBELAJARAN BANGUN GEOMETRI MENGHITUNG VOLUME BALOK - Napitupulu, Eastman; Tambunan, Hardi (JURNAL CURERE, 2023)
The purpose of this study is to explore the integration of mathematics with culture through the traditional musical instrument of the Batak Toba ethnic group, one of which is the "garantung." This research employs a qualitative approach, gathering data through interviews and direct exploration of the garantung musical instrument. Data collection techniques involve observation, interviews, and documentation. The findings of this study reveal that the garantung musical instrument encompasses mathematical concepts, specifically in the realm of geometry, including plane and solid geometry. The garantung can serve as a tool to introduce mathematical concepts, such as geometric concepts, to learners, enabling them to better understand abstract mathematical ideas. Moreover, the garantung musical instrument can be utilized as a learning resource in educational settings. However, its usage has become increasingly rare within the context of modern musical development.Furthermore, there is a need for further research to develop mathematics teaching materials rooted in the Batak Toba culture, particularly focusing on the garantung musical instrument. This study highlights the potential for harmonizing traditional cultural elements with mathematical education, offering an innovative approach to teaching and learning that enriches both fields.